Optimization of RFID Network Planning Using MDB-FA Method - Elewe, Adel Muhsin; Hasnan, Khalid; Nawawi, Azli (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Topology network design in RFID Network Planning (RNP) is the most important factor in hard optimization problems of network planning. Reader distribution is highly impacted by topological tags distribution. The integration of RFID multi-objective network planning with the network topology design results in better capability of reader distribution. Thus, this paper evaluates the impact of topological network design to support the RFID reader’s distribution system. Monte Carlo simulation (MCS) is used to generate tag distribution based on network topology design modules as a method to evaluate the deterministic indicators in NP-hard problems. The generated data are utilized as an input representation to apply into firefly algorithm based on Density- Based Algorithm (DBSCAN) to find the optimal network solution. Experimental results show the effectiveness of the method in L-Shape RNP, and show that the proposed algorithm is capable of achieving high coverage and use of fewer readers in actual conditions of warehouse design.